Obstetric Danger Signs: Knowledge, Attitude, Health-Seeking Action, and Associated Factors among Postnatal Mothers in Nekemte Town, Oromia Region, Western Ethiopia-A Community-Based Cross-Sectional Study - Misganu Teshoma Regasa; Jote Markos; Ashenafi Habte; Shivaleela P. Upashe (Hindawi Limited, 2020)
Background. Maternal mortality remains unacceptably high due to pregnancy complications and remains the major health problems in many developing countries such as Ethiopia. Having poor knowledge of obstetric danger signs contributes to delays in seeking and receiving skilled care which in turn increases maternal mortality. However, in Ethiopia, studies are lacking regarding the knowledge level of mothers about obstetric danger signs during pregnancy, child birth, and postnatal periods. In Ethiopia, the proportion of those who have full knowledge of these obstetric danger signs during pregnancy, child birth, and postnatal period is not known. Despite few studies are conducted at health facility level focusing on danger signs during pregnancy, the issue of health-seeking action after identifying danger signs and attitude of mothers towards obstetric danger sign was not addressed. Objectives. To determine knowledge, attitude, health-seeking action towards obstetric danger signs, and associated factors among postpartum women. Methods.A community-based cross-sectional study was conducted in Nekemte Town from October 1 to November 30, 2017. Multistage sampling technique was employed to select the total sample size of 621. Ethical clearance was obtained from Wollega University research and ethical committee. A pretested structured questionnaire was used to collect data from respondents. Data were entered to EpiData version 3.1 and exported to SPSS version 20 for analysis. To assess the associations between dependent and independent variables, binary and multivariate logistic regressions were employed, and the strength of association was presented using odds ratios with 95% confidence intervals. Result. Only 197 (32.3%) of respondents were able to spontaneously mention at least five key obstetric danger signs during antepartum, intrapartum, and postpartum (in the three phases) with at least one obstetric danger sign in each phase and thus were considered as having good knowledge of key obstetric danger signs. Government employee (AOR = 3.28, 95% CI: 1.98-5.42), able to read and write (AOR = 4.92, 95% CI: 2.14-11.3), primary school (AOR = 4.90, 95% CI: 2.11-11.4), ANC follow-up (AOR = 6.2, 95% CI: 1.82-21.21), and ANC visit (AOR = 4.07, 95% CI: 2.35-7.06) were significantly associated with knowledge of obstetric danger sign. From 150 (24.6%) participants who faced obstetric danger signs during their last pregnancy, the majority of them, 137 (91.3%), had a good practice which is seeking a health facility for care. Conclusion and Recommendation. Despite their low knowledge level and attitude, the practice of mothers in response to obstetric danger signs was encouraging. Occupation, educational status, ANC follow-up, and number of ANC visits were variables significantly associated with knowledge of obstetric danger signs. Health care providers should provide health education and counseling to increase awareness, and appropriate counseling during antenatal care at each visit is of paramount importance.